Diffusion of low carbon innovation among Indian foundries: lessons from the improved divided blast cupola. (2016) - Yap, Nonita T.; Vaidyanathan, Geeta; Pal, Prosanto; Sethi, Girish; Joshi, Veena
India's foundry industry is an important source of export earnings and among its biggest generators of employment. Energy consumption contributes 12-15% of total production cost, making energy efficiency innovations critical for a foundry's profitability. Pressure for cleaner and energy efficiency innovations emerged in the early 90s following successful public litigation over acid and particulate emissions of foundry operations. Limits on suspended particulate matter had been set in the 80s but not systematically enforced. This paper examines the factors contributing to the favourable rate of diffusion of an improved divided blast cupola among India's small and medium foundries from 1994 to 2013. The findings suggest that diffusion of innovation programs need to be framed within the decision process of the firm. Programs need to be designed in terms of what that can trigger the firm's decision process and nudge it from problem recognition to adoption.